Investigation of the canine elbow joint innervation in 100 joints - Jowita Jacewicz; Waldemar Sienkiewicz; Tomasz Burzykowski; Beata Degórska (PLoS ONE, 2025)
The canine elbow joint is innervated by four nerves: the musculocutaneous, median, radial, and ulnar nerves. There is little data in the veterinary literature examining the course of the articular branches of those nerves. There is also no agreement as to their anatomical location in the joint capsule nor to their number. The lack of such data prompted us to undertake studies to analyze the course of these nerves and the number and location of their articular branches in both left and right joint capsules in 50 dogs (with a total of 100 joints). No within-individual differences in the number of branches or their location were found between left and right joints. There was between-joint variation in the number of articular branches of the median, musculocutaneous, and radial nerves. There was also variation in the location of the branches of the median and radial nerves. Some of the results are different from those previously reported in the literature. The obtained data allow to further detail anatomical descriptions of the dog elbow innervation. Additionally, they may constitute the basis for developing new surgical procedures, improving existing procedures, or allow a better preparation for possible differences during operations of this joint.